Development process of green logistics - Shevchenko, Yana (My University, 2014)
Logistics is the integrated management of all the activities required to move products through the supply chain. For a typical product this supply chain extends from a raw material source through the production and distribution system to the point of consumption and the associated reverse logistics. The logistical activities comprise freight transport, storage, inventory management, materials handling and all the related information processing.
Keywords: green logistics; move products; development; зелена логістика; переміщення товарів; розвиток; развитие; перемещения товаров; зеленая логистика